Development of high-performance and cost-effective electrode assembly for redox flow batteries - Přemysl Richtr; Tobias Gerber; Peter Fischer; Jiří Charvát; Christian Ress; Jens Noack; Björn Hage; Miloš Svoboda; David Gráf; Jan Beneš; Petr Mazúr (Results in Engineering)
Redox flow batteries (RFBs) offer promising solutions for safe and durable stationary energy storage; however, high capital expenditures (CAPEX) hinder their commercialization. We developed a method for low-contact resistance welding of carbon-polymer composite plates to graphite felt electrodes and copper current collectors. Using our own extruded carbon-polymer composite plate with low carbon filling, we optimized two manufacturing methods: traditional hot-press and novel microwave welding. Electrode assembly samples were characterized by dry electric resistance measurements at compression ratios (CR) of 5–45 %, complex microstructural analysis via X-ray micro-computed tomography and scanning electron microscopy, and electrochemical characterization in a lab-scale vanadium RFB using voltammetry techniques, electrochemical impedance spectroscopy, and galvanostatic charge-discharge cycling both in a single-cell and two-cell stacks. Hot-press welding significantly improved overall battery performance by reducing contact resistance up to 2.5 times compared to non-welded assemblies. At 10 % CR, the performance of developed assemblies matched commercial unbonded materials at 20 % CR, using a carbon-polymer composite plate with higher conductive filler content. Achieved stack parameters included area-specific resistance of 2.1 Ω cm2 per cell and energy efficiency of 86.9 % at 40 mA cm–2. Developed electrode assemblies remained stable after 800 cycles. Microwave welding enabled faster production of electrode assemblies with similar performance to hot-press welded ones. The developed electrode assemblies, based on low-filled carbon-polymer composite plate may substantially reduce battery stack costs and assembly complexity, leading to lower levelized cost of storage and more reproducible RFB fabrication.